2017
DOI: 10.3389/fphys.2017.00810
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sport-Specific Training during the Early Stages of Long-Term Athlete Development on Physical Fitness, Body Composition, Cognitive, and Academic Performances

Abstract: Introduction: Several sports demand an early start into long-term athlete development (LTAD) because peak performances are achieved at a relatively young age (e.g., gymnastics). However, the challenging combination of high training volumes and academic demands may impede youth athletes' cognitive and academic performances. Thus, the aims of this study were to examine the effects of a 1-year sport-specific training and/or physical education on physical fitness, body composition, cognitive and academic performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 36 publications
(66 reference statements)
2
36
1
1
Order By: Relevance
“…A atenção é limitada e apresenta seus níveis em variação ao longo do dia, o comprometimento deficitário em algum momento isolado não corresponde a declínio dessas funções (Budde et al, 2012;Granacher & Borde, 2017;Lambrick et al, 2016).…”
Section: Discussionunclassified
“…A atenção é limitada e apresenta seus níveis em variação ao longo do dia, o comprometimento deficitário em algum momento isolado não corresponde a declínio dessas funções (Budde et al, 2012;Granacher & Borde, 2017;Lambrick et al, 2016).…”
Section: Discussionunclassified
“…There are wide range of studies reporting that physical activity level is a good indicator of better body composition and physical fitness capacity (Çetin et al, 2018;Janssen et al, 2010;Granacher and Borde, 2017;Polat and Gunay, 2016;Vanttinen et al, 2011;Ara et al, 2004;Ara et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Granacher and Borde (2017), examined the physical fitness and body composition among prepubertal children. They reported that participants in the elite sports class had a lower BMI (22%), lower body fat mass (14%), and more relative skeletal muscle mass (6%) than those of the control group.…”
Section: Discussionmentioning
confidence: 99%
“…The 6-min run test requires pupils to run as far as possible for 6 min and it was used to assess cardiorespiratory fitness [22,23]. Students were instructed to run on a circuit in the gym and the distance covered by each participant was measured in meters.…”
Section: Assessmentmentioning
confidence: 99%
“…Students were instructed to run on a circuit in the gym and the distance covered by each participant was measured in meters. The test had an intraclass correlation coefficient of 0.86 in children aged 6-10 years [22].…”
Section: Assessmentmentioning
confidence: 99%